2017
DOI: 10.1038/srep41358
|View full text |Cite
|
Sign up to set email alerts
|

Clomipramine causes osteoporosis by promoting osteoclastogenesis via E3 ligase Itch, which is prevented by Zoledronic acid

Abstract: Patients taking antidepressants, including Clomipramine (CLP), have an increased risk of osteoporotic fracture. However, the effects of CLP on bone metabolism are unknown. Here, we demonstrate that WT mice treated with CLP for 2 weeks had significantly reduced trabecular bone volume and cortical bone thickness, associated with increased osteoclast (OC) numbers, but had no change in osteoblast numbers or bone formation rate. Bone marrow cells from CLP-treated mice had normal OC precursor frequency, but formed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Adjacent sections were also stained for TRAP activity to identify OCs. Histomorphometric analyses were performed on sections cut at three levels in each sample using CMSR SOPs . In brief, stained sections were numbered blindly and were converted to digital images using an Olympus VS120 whole slide imaging system (Olympus, Center Valley, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent sections were also stained for TRAP activity to identify OCs. Histomorphometric analyses were performed on sections cut at three levels in each sample using CMSR SOPs . In brief, stained sections were numbered blindly and were converted to digital images using an Olympus VS120 whole slide imaging system (Olympus, Center Valley, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Histomorphometric analyses were performed on sections cut at three levels in each sample using CMSR SOPs. (36,37) In brief, stained sections were numbered blindly and were converted to digital images using an Olympus VS120 whole slide imaging system (Olympus, Center Valley, PA, USA). A full static bone histomorphometric analysis in long bone, including BV/TV (%), Tb.Th (μm), Tb.N (/mm), Tb.Sp (mm), osteoblast surface/bone surface (Ob.S/BS; %), osteoclast surface/bone surface (Oc.S/BS; %), and eroded surface/bone surface (ES/BS; %), were performed in the secondary spongiosa area using the automated algorithm with a Visiopharm Image Analysis System as we previously described.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…Histomorphometric analyses were performed on sections cut at 3 representative levels in each bone. The percentage of trabecular bone (BV/TV) was analyzed using the automated algorithm we developed with the Visiopharm Image Analysis System [ 14 ]. (2) The frozen sections (8 μm) were cut using a Leica CM1850 cryostat (Leica, German) and mounted with a mounting medium containing DAPI (Vector Lab., Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Many experiments have demonstrated that ZA inhibits bone destruction caused by enhanced differentiation and function of osteoclasts by interrupting RANKL/RANK pathway [ 17 , 18 , 38 ] (Fig. 1 ).…”
Section: Inhibition Of Differentiation Of Osteoclasts By Zamentioning
confidence: 99%
“…ZA decreases the expression of RANK to inhibit the differentiation of osteoclasts through suppressing TNF-α and RANKL [ 39 41 ]. In addition, it is reported that ZA also inhibits NFATc1 and c-fos [ 17 , 26 , 42 ], suppresses NF-κB pathway through promoting the deubiquitination of TRAF6 [ 18 ], as well as the phosphorylation of tyrosine and the nuclear translocation of p65 [ 43 ].
Fig.
…”
Section: Inhibition Of Differentiation Of Osteoclasts By Zamentioning
confidence: 99%